A GOOFY GLOSSARY FOR ACCOUNTANTS. - Singer, Frank A. (The Accounting Review, 1958)
The article presents a list of sarcastic words given by college students in the U.S. to the journal "The Accounting Review." The author of the article requested a class of college students to bring in a list of terms which they felt might be misunderstood. The result was not only what the author expected, but many definitions of the outlandish character which his own example had suggested. Since the authorities of the journal wanted some amusement and since some ingenuity was apparent, they set out to produce the list reported in the article. They examined the index of the current edition of the "Accountants Handkook," and, after selecting the terms produced a list. Some of the words are: Acid-test which is quoted as litmus paper; Accountant is the one without "ecountant," hence a no count; "Accrual" is interpreted as kind; "Allowance for containers" is usually a nickle on each bottle; "Annual Reports are quoted as Independence Day celebrations," "Deferred charges," are quoted as shepherd's flock after shearing.